Notes on the feasibility of automatic warehousing - Kay, E.; Pemberton, A. W. (College of Aeronautics, 1968)
There is now sufficient information and experience available on the subject of automatic warehousing to make it possible for an organisation with major storage problems to assess the advantages and disadvantages of investing in one of these highly sophisticated systems provided it examines its requirements systematically and in detail. Additionally, it is becoming possible to compute the relative cost advantages of this kind of storage pattern as against the conventional one (i.e. Fork Lift Trucks and Pallet Handling). We believe that the present position regarding the feasibility of automatic warehousing is untenable to most organisations. There is, so far as we know, no detailed guide available or published which enables any organisations to make even a preliminary examination of the possible advantages of fully automated storage. From the theoretical work carried out at the Materials Handling Research Unit* we can now derive rules by which the various factors influencing feasibility can be measured and valid comparisons be made. The detailed application of these rules is likely to vary from case to case, and it would be impossible to comprehensively describe their use in a short and nontechnical publication. The notes which follow are not to be regarded as rigid guide lines, but attempt to set out the criteria by which an organisation may judge its own readiness to accept a change to mechanised storage.